MANUFACTURING AND TESTING OF SIT-TO-STAND EXOSKELETON FOR PARAPLEGIC PATIENTS - Maulana, Fakhri
Around 22.5 million people in Indonesia in 2020 are person with disabilities. From that 22.5 million people, around 38.3% have a disability that affect lower body movement such as standing, walking, or climbing stairs. Meanwhile, assistive device that can replace movement function in Indonesia are still relatively few and are expensive in the international market. The Biomechanics FTMD ITB research team has developed and designed an active assistive device for sitting to standing movements. However, the tool has not been fabricated and the capabilities of the tool have not been tested. Therefore, in this undergraduate project fabrication and testing is carried out. The work starts from reviewing the design to see whether has been made are affect the testing. Then proceed with the production of exoskeleton consisting of fabrication and assembly. After the exoskeleton is made, exoskeleton will be tested with 2 modes, testing without able-bodied subject and with able-bodied subject. Testing will be carried out using motion capture method to obtain the trajectory of exoskeleton when exoskeleton is use with and without able-bodied subject. Trajectory that been created from data motion capture processing when testing without able-bodied have similar trendline and little error if compare with encoder sensor. While trajectory that been created from testing with able-bodied subject have an error about 10 degreee in the hip section. This error is cause by obstruction of flexion movement in the hip due to the lack of space between the user’s abdomen and the user’s thighs.